Anticipation in soccer: skilled players benefit from early pattern recognition in corner kick situations - Ivosevic, Lovro; Stöckel, Tino (Frontiers in Psychology, 2025)
Anticipation is a crucial cognitive skill for decision making in life. Especially in sports, such as soccer, accurately anticipating the next play of the opposing team can have a huge impact on the result of a game or individual success in certain situations. This study investigates the differences between skilled players and less-skilled players in anticipating corner kicks by using temporal and spatial occlusion paradigms to figure out, which visual cues are utilized. We presented 171 video scenes of realistic corner kicks - stopped at three time points (150 ms before ball, at ball contact, 150 ms after ball contact) - to 23 skilled soccer players and 23 less-skilled players. Participants had to predict the horizontal landing position of the ball. To examine the effectiveness of different visual cues, participants saw the respective corner kick in full detail (control condition), or with either the kicker or the attacking players being blurred. Results showed that predictive accuracy increases over time and is higher in skilled players than in less-skilled players. Further, it appears that skilled players use information from the attacking players (i.e., pattern recognition) to estimate the landing position. Information of the kicker was not sufficient for neither the skilled players nor the less-skilled players. Our data strongly suggests, that expert soccer players´ advantage over less-skilled players in anticipating the landing position of corner kicks results from their ability to recognize patterns of play. Again, these findings highlight the importance of prolonged times of sport-specific deliberate practice for athletes’ predictive accuracy, and performance and success in general. Findings from this study could inform training regimes in soccer. By guiding players attention to useful visual cues (e.g., pattern recognition) while practicing set-pieces should help them to improve their anticipation skills. Future studies should explore these effects for situations like other set pieces or team-tactics.